Anemia and Low Birth Weight Risk After Fe Therapy in Pregnancy, Puskesmas Kecamatan Kebayoran Baru - Dyah Ponco Sudarmaningsih; Febrial Hikmah; N Sri Widada; Rustiana Tasya Ariningpraja (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2021)
Physiological changes in pregnant women have an impact on reducing the hemoglobin (Hb) level so that they can experience anemia. Anemia in pregnant women is still a high case and be one of the factors of low birth weight (LBW). Iron (Fe) is consumed routinely is thought to help reduce the risk of anemia, but it's still not known yet between the relation of Fe consumed to LBW incidents. Data were taken by cross sectional as many as 150 samples of pregnant women. The results obtained that 56% of pregnant women had anemia. After Fe therapy doses 60-120 mg/day, Hb levels increased by 0.3 g/dL. Although there were significant differences before and after Fe therapy in pregnant women with anemia, about 74% of pregnant women still had experience anemia despite Fe therapy. Provision of Fe therapy for pregnant women either with a dose of 60-120 mg/day, had not been effective enough in increasing Hb levels. LBW cases were also found in this study, which is around 9.3%. Pregnant women with anemia have a higher risk of LBW. This indicates that offering Fe to pregnant women has not been effective.Â